WASp Is Essential for Effector-to-Memory conversion and for Maintenance of CD8+T Cell Memory - Liu, Qiao; Zhang, Liang; Shu, Zhou; Yu, Tingting; Zhou, Lina; Song, Wenxia; Zhao, Xiaodong (Frontiers in Immunology, 2019)
Wiskott-Aldrich syndrome (WAS) is a rare X-linked primary immunodeficiency characterized by recurrent infections, micro thrombocytopenia, eczema, and a high incidence of autoimmunity and malignancy. A defect in the T cell compartment is thought to be a major cause of immunodeficiency in patients with WAS; However, whether the antigen specific T memory cell is altered has not been extensively studied. Here, we examined the expansion/contraction kinetics of CD8+ memory T cells and their maintenance in WASp-/- mice. The results showed that WAS protein (WASp) is not required for differentiation of CD8+ effector T cells; however, CD8+ T cells from WASp-/- mice were hyperactive, resulting in increased cytokine production. The number of CD8+ T memory cells decreased as mice aged, and CD8+ T cell recall responses and protective immunity were impaired. WASp-deficient CD8+ T cells in bone marrow chimeric mice underwent clonal expansion, but the resulting effector cells failed to survive and differentiate into CD8+ memory T cells. Taken together, these findings indicate that WASp plays an intrinsic role in differentiation of CD8+ memory T cells.